2016
DOI: 10.1152/ajpregu.00516.2015
|View full text |Cite
|
Sign up to set email alerts
|

Positive airway pressure improves nocturnal beat-to-beat blood pressure surges in obesity hypoventilation syndrome with obstructive sleep apnea

Abstract: Positive airway pressure (PAP) treatment has been shown to have a modest effect on ambulatory blood pressure (BP) in patients with obstructive sleep apnea (OSA). However, there is a paucity of data on the effect of PAP therapy on rapid, yet significant, BP swings during sleep, particularly in obesity hypoventilation syndrome (OHS). The present study hypothesizes that PAP therapy will improve nocturnal BP on the first treatment night (titration PAP) in OHS patients with underlying OSA, and that these improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…They demonstrated that BP variability during sleep acutely decreased while CPAP was applied, 39 , 46 , 114 which is a consequence of a reduction in the number of BP peaks. 115 Furthermore, beat-by-beat BP variability before CPAP initiation was higher than immediately after CPAP withdrawal, following an approximately 5-month treatment period, 116 in agreement with the observation of lower postapneic BP peaks at CPAP withdrawal. 50 A second group of studies used ABPM and analyzed the change in 24-hour BP variability.…”
Section: Bp Variability In Osasupporting
confidence: 73%
“…They demonstrated that BP variability during sleep acutely decreased while CPAP was applied, 39 , 46 , 114 which is a consequence of a reduction in the number of BP peaks. 115 Furthermore, beat-by-beat BP variability before CPAP initiation was higher than immediately after CPAP withdrawal, following an approximately 5-month treatment period, 116 in agreement with the observation of lower postapneic BP peaks at CPAP withdrawal. 50 A second group of studies used ABPM and analyzed the change in 24-hour BP variability.…”
Section: Bp Variability In Osasupporting
confidence: 73%
“…28,30,31,32 Several small studies with 1 night or up to 3-month follow-up periods have evaluated such PAP interventions. 29,30,[33][34][35] The first prospective study on 23 patients was conducted by Banerjee et al, demonstrating the correction of obstructive events and improvement in sleep architecture during the first CPAP titration night, although a failure to correct nocturnal hypoxemia was noted in 43% of the patients. 33 An observational study of 29 patients with OHS treated with CPAP found progressive improvements in mean nocturnal SpO 2 and daytime CO 2 over a 3-month period.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the benefit of PAP adherence on PaCO 2 level (an average drop of 1.5 mmHg per average hour of nightly PAP use) and SF-36 seems also to continue after 6 hours of nightly PAP use. Furthermore, Carter and colleagues 35 in a substudy of a randomized controlled trial in OHS patients found that PAP adherence over a 6-week period had a marked effect on improving surges in nocturnal blood pressure control as well. Therefore, the importance of close clinical follow-up after PAP therapy is initiated should be stressed to ensure adequate adherence and confirm response to therapy, particularly because poor adherence to PAP therapy has also been associated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent study, the same group demonstrated that as little as one night of CPAP significantly improved nocturnal baroreflex function 20. More recently, our laboratory used finger plethysmography to quantify the number of nocturnal surges in beat-to-beat BP in 17 patients with hypercapnic OSA 21. Indeed, in these patients who at baseline had relatively well-controlled BP during the daytime, there was no change in daytime office BP after 6 weeks of PAP therapy.…”
mentioning
confidence: 97%